An Encrypted Log File Keylogger System for Parental Control - S. Li, L; M. Fauzee, Z; Zamin, N; Kamarudin, N; A.Sabri, N; S.Nik Ab Aziz, N (International Journal of Engineering and Technology, 2018)
Keystroke logging, often referred to as keylogger, keylogging or keyboard capturing, is the process of recording all the pressed keys on a keyboard autonomously so that the person who is using the keyboard is unaware that their actions on the computer are being monitored.Â In the world of cyber-crime, keylogger tool has been used mostly for malicious purposes such as stealing personal information and credit card details. However, for ethical purposes, keylogger can be useful in terms of monitoring userâ€™s activities without being noticed. For instance, parents can use keylogger to monitor their childâ€™s activity on the web. The log file is used to store the recorded keystrokes.Â However, current log files in keylogger are not encrypted, which can be easily hacked for malicious purposes. This paper proposes a new software based keylogger with log file encryption to increase the keylogging security towards Industrial Revolution 4.0.Â